2006
DOI: 10.1007/s00114-006-0152-8
|View full text |Cite
|
Sign up to set email alerts
|

Domino syntheses of bioactive tetronic and tetramic acids

Abstract: Natural products containing tetronic acid or tetramic acid moieties continue to attract the interest of chemists, biologists, and physicians due to their challenging structures and to the wide range of biological activities they display. This review portrays the structural varieties of tetronic and tetramic acids and the spectrum of possible therapeutically relevant effects in man for exemplary derivatives. Their biosynthetic origin from alpha-amino and alpha-hydroxy acids is briefly discussed as is the relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
30
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(31 citation statements)
references
References 56 publications
(47 reference statements)
0
30
0
1
Order By: Relevance
“…[1] They include spiro-A C H T U N G T R E N N U N G tetronic acids, [2][3][4][5] such as the antitumour compound chloro-A C H T U N G T R E N N U N G thricin (1; [2] Figure 1) and the protein phosphatase inhibitor RK-682 (2). [6] Particular interest attaches to the tetronate polyethers tetronomycin (TMN) 3 [7] and tetronasin (TSN) 4 [8] because, although they are chemically almost identical, they differ from one another in their configuration at every one of ten comparable asymmetric centres ( Figure 1).…”
Section: Introductionmentioning
confidence: 97%
“…[1] They include spiro-A C H T U N G T R E N N U N G tetronic acids, [2][3][4][5] such as the antitumour compound chloro-A C H T U N G T R E N N U N G thricin (1; [2] Figure 1) and the protein phosphatase inhibitor RK-682 (2). [6] Particular interest attaches to the tetronate polyethers tetronomycin (TMN) 3 [7] and tetronasin (TSN) 4 [8] because, although they are chemically almost identical, they differ from one another in their configuration at every one of ten comparable asymmetric centres ( Figure 1).…”
Section: Introductionmentioning
confidence: 97%
“…6) These isolated compounds exhibit a wide range of biological and pharmaceutical activities 7,8) (including potent antibiotic 6,9) and antiviral 10,11) properties, mycotoxicity, 12) and cytotoxicity [13][14][15][16][17][18] ) and have attracted much attention of chemists, physicians, and biologists. 19,20) Biosynthetic studies have shown that the tetramic acid ring (2,4-pyrrolidinedione ring) is formed from a C 2 unit, and the nitrogen atom and the remaining two carbon atoms are derived from an amino acid. 21) All the 3-acyl tetramic acids can be considered as the results from the substitution of the hydrogens of C-5 with other functional groups and the substitution of the methyl group of C-7.…”
mentioning
confidence: 99%
“…20 The entire synthetic route was efficient and simple. The cyclization of compound 2 was not a usual Lacey-Dieckmann reaction, 21 but rather an esterification. The ester group and the tert-butoxy group in compound 2 were converted to the carboxyl and hydroxyl group separately under acidic conditions.…”
Section: Introductionmentioning
confidence: 99%